Direitos à moradia e à preservação ambiental na cidade de Boa Vista - RR - Ignácio, Rozane Pereira (2019)
The organization of the urban space of Boa Vista - RR is the result of a complex of constraints and through this research the process of occupation of the banks of the urban streams, its relation with the social inequalities and the administrative, civil and penal implications arising from the Occupy these spaces called permanent preservation areas - APPs. The starting point is the identification of the urban streams Caranã, Caxangá, Frasco, Grande, Mirandinha and Pricumã, which measure up to 10 (ten) meters wide and for the Forest Code it is obligatory to maintain, without any occupation, a 30 (thirty) meters width. Identified to irregular occupations is a social and legal conflict between the residents of the margins of APPs and the public power, since on the one hand we have a rigid environmental legislation that establishes measures of protection to the environment and sanctions to those that cause damage to the environment Environment and on the other, we have the needy population who have as fundamental guarantee the right to housing. In order to understand the relationship between law and geography, Geodireito is used to explain the regulation of river occupation in urban spaces and the implications of the irregular use of APPs in the Roraima legal system and the consequent judicialization of these socio-environmental conflicts.